A Juridical Study of Granting Wills to Heirs in the Perspective of Islamic Inheritance Law - Moechthar, Oemar; Sekarmadji, Agus; Katherina, Ave Maria Frisa (Yuridika, 2022)
This paper is intended to criticize the societal practices that occur, especially in Indonesia, where many heirs during their lifetime give wills to heirs who have been given a particular part in the Qur'an, which results in other (experts) heirs not getting a share or obtaining. Less than that specified in the Qur'an. One of the contributing factors is because, according to the heir, the provision of the will is to provide justice for all his heirs; however, fairness according to the heir is different from justice in the distribution of inheritance according to the Al-Qur'an and Hadith. Legal research uses this case approach as the primary analysis juxtaposed with the statutory approach and the conceptual approach as the 'knife' of analysis. The thesis or argument obtained is related to aspects of Islamic law; it is not appropriate for the heir to give a will to someone who is an heir whose part has been assigned in the Al-Quran and Hadith.